Learners’ Goal Profiles and their Learning Patterns over an Academic Year - Ng, Clarence (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
The present study aimed to examine distance learners’ goal profiles and their contrasting patterns of learning and achievements at three different points during an academic year, i.e. in the beginning of the course in relation to learners’ general orientations to learning, at the middle of the course in relation to learners’ completion of an assignment, and towards the end of the course in relation to learners’ preparation for course examination. Two hundred seventy-six adult distance learners completed three survey questionnaires that assessed their motivation and learning at these three learning points. Using person-centred analytical procedures, this study located four groups of learners based on different combinations of mastery and performance-approach goals. MANOVA results have shown that multiple-goal learners (High mastery/High performance, HH) who held strong mastery and performance-approach goals used more deep and regulatory strategies and showed a higher level of learning interest across three waves of surveys than did those focusing solely on mastery (HL) or performance-approach goals (LH). However, the multiple-goal learners did not have better achievement levels compared to those focusing solely on mastery goals (HL). Given that multiple goal learners learnt with a more engaged pattern, it is less likely that these motivated learners will drop out of distance learning courses and programs. Future studies should explore how these goals can be promoted simultaneously in distance learning.